Building integration of active solar energy systems for façades renovation in the urban fabric: Effects on the thermal comfort in outdoor public spaces in Naples and Thessaloniki. (May 2022) - Vassiliades, C.; Savvides, A.; Buonomano, A.
Abstract: In 2030, 80% of the world's population will live in cities, when cities are responsible for over 70% of global carbon dioxide emissions. As the built environment accounts for 40% of the global primary energy consumption, changes need to take place towards the energy sustainable transition. The above, combined with Europe's aging building stock, bring the energy renovation and the building integration of active solar systems on existing buildings to the forefront of discussions. The research performed herein, investigates the effects on thermal comfort in public spaces caused by the building integration of active solar energy systems on existing facades in two coastal cities, Naples, Italy and Thessaloniki, Greece, using the Physiological Equivalent Temperature. A typical example of the urban system of each city is chosen, and active solar systems are integrated on the buildings' facades. The thermal conditions on the street level are then simulated by the means of Envi-MET software. The aim is to compare the thermal conditions in the public space, before and after the integration, evaluated through different filters of solar urban planning/building integration of active solar systems, and subsequently focusing to propose the most viable combination of urban practice and building integration strategy. Highlights: Integration of a BIPVs for energy retrofitting of existing buildings. Thermal conditions on the street level simulated with Envi-MET. Effects on thermal comfort in public spaces caused by building integration of PVs. Proposal of the most viable combination of building integration strategy. Use of Physiological Equivalent Temperature (PET) to evaluate thermal conditions.